Self-DNA Sensing by cGAS-STING and TLR9 in Autoimmunity: Is the Cytoskeleton in Control? - Amadio, Roberto; Piperno, Giulia Maria; Benvenuti, Federica (Frontiers in Immunology, 2021)
The presence of nucleic acid (NA) in endosomes and cytosol of mammalian cells signals for potential infections and induces activation of inflammatory cytokines via DNA sensors such as TLR9 and cGAS-STING. These pathways can be triggered as well by NA of self, not pathogenic origin causing unwanted inflammation that may lead to autoimmunity. Fine-tuned membrane trafficking, cellular compartmentalization and specific molecular mechanisms cooperate to balance activation of DNA sensors. Yet self-DNA is emerging as a central driver of multifactorial and monogenic autoimmune diseases. The challenge is particularly complex for cells of the monophagocytic system that ingest large amounts of apoptotic self-DNA and DNA in large macromolecular complexes. This review provides an update on recent advances in the field of self-DNA recognition with a special focus on membrane trafficking and integration between endosomal and cytosolic DNA sensors in phagocytes, together with examples of human diseases arising from deviations in these processes. A special focus is given to the emerging role of the actin cytoskeleton as a master regulator of cellular responses to self-DNA. Prototypical actin related diseases such as Wiskott-Aldrich syndrome were recently associated to dysregulated cGAS-STING functioning and more actin-dependent processes that interfere with self-DNA sensing are likely to emerge in this disease. We anticipate that other primary immune deficiencies caused by mutations in actin regulators may entail deregulation of DNA sensing by mis-sorting of DNA receptors or altered compartmentalization/trafficking of ligands.